2020
DOI: 10.15376/biores.15.3.4781-4801
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of a xylan-based antibacterial papermaking additive to protect against Escherichia coli bacteria

Abstract: A xylan-based antimicrobial additive agent was prepared and studied for use in paper products against Escherichia coli bacteria. The derived cationic-xylan-grafted-guanidine polymer (CX-g-PHGH) was successfully synthesized by graft copolymerization of cationic-xylan with polyhexa-methylene guanidine hydrochloride (PHGH) using ceric ammonium nitrate as an initiator. The obtained CX-g-PHGH had a maximum PHGH grafting ratio of 18.4% and efficiency of 58.4% and showed good viscosity and thermal stability. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…However, native xylan-and acetylated xylan-coated papers exhibited a better inhibitory effect. These results were in accordance with the WVTR values, which were lower for these coated samples, and with previously reported findings, which confirms that, in its native form, xylan hemicellulose exhibits slight antimicrobial effects against pathogenic bacteria [45,46]. tillis has become widely adopted as a model organism, often considered as the Gram-positive equivalent of E. coli, an extensively studied Gram-negative bacterium.…”
Section: Antimicrobial Propertiessupporting
confidence: 93%
“…However, native xylan-and acetylated xylan-coated papers exhibited a better inhibitory effect. These results were in accordance with the WVTR values, which were lower for these coated samples, and with previously reported findings, which confirms that, in its native form, xylan hemicellulose exhibits slight antimicrobial effects against pathogenic bacteria [45,46]. tillis has become widely adopted as a model organism, often considered as the Gram-positive equivalent of E. coli, an extensively studied Gram-negative bacterium.…”
Section: Antimicrobial Propertiessupporting
confidence: 93%
“…The antimicrobial and antifungal properties of xylan films and paper coated with hardwood xylan hemicelluloses have been reported on in other recent studies [25][26][27][28]. It was concluded that, in its native form, xylan shows moderate antifungal activity and slightly antimicrobial effects against pathogen bacteria (E.coli, S. aureus).…”
Section: Introductionmentioning
confidence: 80%
“…The antimicrobial and antifungal properties of xylan films and paper coated with hardwood xylan hemicelluloses have been reported on in other recent studies [25][26][27][28]. It Based on these features, native hemicelluloses alone are usually unable to form strong and durable films.…”
Section: Introductionmentioning
confidence: 93%